The Portuguese Tariffs for Use of Transmission Network - Study on the Implementation of a Marginal Based Term - João Tomé Saraiva (2002)
In 1999 and 2000 the Power Systems Unit of INESC - Porto, Portugal, conducted a consultancy study under a contract with the ERSE - the Portuguese Electricity Regulatory Board - to evaluate the interest of considering alternative cost allocation methods apart from the currently used Postage Stamp to set Tariffs for the Use of Transmission Network. This paper summarizes the main results that where obtained, regarding the eventual integration of a short term marginal based component in those tariffs. It should be clarified that it was not the purpose of this study to question the regulated approved remuneration of the transmission company, but only to consider the potential interest of using alternative cost allocation methods, regarding the current Postage Stamp tariffs.